Male and female differences in the use of social media for learning purposes. Issue 5 (3rd September 2018) - Akman, Ibrahim; Turhan, Cigdem
ABSTRACT: This study aims to explore the differences between male and female users' behaviour with regard to acceptance of social media for learning in higher educational institutions. For this purpose, a survey was conducted and the least square regression analysis approach was utilised to investigate the relationships among the constructs in the research model for male and female users from a general and ethical perspective, focusing on the reliability, performance and awareness factors. The findings from the analysis reveal that a significant degree of diversity is present in the factors represented by 'general reliability', 'ethical reliability', 'ethical performance', 'ethical awareness' and 'ethical intention'.